2002
DOI: 10.1093/neucas/8.3.233
|View full text |Cite
|
Sign up to set email alerts
|

Is There a Schizophasia? A Study Applying the Single Case Approach to Formal Thought Disorder in Schizophrenia

Abstract: It has been suggested that formal thought disorder, the incoherent speech of schizophrenia, may involve a language disturbance among other abnormalities, or even be a form of dysphasia. Six patients with and seven without formal thought disorder were evaluated on an aphasia test battery. Spontaneous speech was also analysed using Brief Syntactic Analysis. Poor performance on the aphasia test battery was found to be associated with general intellectual impairment but not with formal thought disorder. Naming was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
3
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 18 publications
3
45
3
5
Order By: Relevance
“…The pattern of intrusion errors, which have been linked to thought disorder (Oh, McCarthy, & McKenna, 2002), and were also found on regular and novel but not irregular verbs, may also be consistent with this view. The results appear to be inconsistent with claims that thought disorder reflects a general cognitive dysfunction (see Introduction), since any general dysfunction seems unlikely to affect regular and novel verbs differently from irregular verbs, particularly given the factors controlled for in the present study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…The pattern of intrusion errors, which have been linked to thought disorder (Oh, McCarthy, & McKenna, 2002), and were also found on regular and novel but not irregular verbs, may also be consistent with this view. The results appear to be inconsistent with claims that thought disorder reflects a general cognitive dysfunction (see Introduction), since any general dysfunction seems unlikely to affect regular and novel verbs differently from irregular verbs, particularly given the factors controlled for in the present study.…”
Section: Discussionsupporting
confidence: 65%
“…Oh and McKenna (2002) suggested that intrusion errors in expressive speech (not just semantic associates but also unrelated words) may reflect a semantic deficit in schizophrenia, possibly related to the disorganization of lexical/semantic knowledge discussed in other studies. On the one hand, such a semantic deficit does not seem to fully explain the pattern of intrusion errors, since it would predict higher rates for patients than controls on both real regular and real irregular verbs (and possibly for novel verbs too, if the errors reflect an attempt to “make sense” of the novel input).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…O. Chaika & Alexander, 1986; Maher, 1972, 1983; Rodriguez-Ferrera, McCarthy, & McKenna, 2001). One possible explanation for conflicting findings was offered by Oh et al (Oh, McCarthy, & McKenna, 2002), who showed that syntactic errors occurred independent of thought disorder in schizophrenics, whereas semantic anomalies were strongly associated with the presence of thought disorder. Thus, stratifying schizophrenics on the basis of the presence or absence of thought disorder may be essential for distinguishing linguistic correlates of schizophrenia from linguistic correlates of schizophrenic thought disorder.…”
Section: Thought Disorder Language Disorder Speech Disorder and Comentioning
confidence: 99%
“…In particular, there is no anomaly at the lexical level: the words themselves are not being used in an unusual or novel way – in the first example the patient is talking about the same person as we do when we refer to Jesus, and the meanings of wine glass, stomach, the Mafia and killing are likewise entirely conventional. Nor does there seem to be any obvious violation of so-called selectional requirements, the constraints on how the individual parts of sentences can be coupled – we are not dealing with the kind of statements uttered by patients with formal thought disorder (the incoherent speech of schizophrenia) such as “The trains broke and the pond fell in the front doorway” (Oh, McCarthy, & McKenna, 2002), where the lexical features of ponds do not allow them to fall in doorways. Rather, (1)–(3) are pathological by virtue of, and only of, the way in which different sentence parts are combined at the level of propositional or grammatical meaning , where we see referential forms of meaning transpiring within specific grammatical configurations.…”
Section: Applying the Un-cartesian Hypothesis To Delusionsmentioning
confidence: 99%